THE ROLE OF NURSING IN IMPROVING TREATMENT ADHERENCE AMONG PATIENTS WITH DIABETES. - Nuwair Qalib Al-Ruwaili, Shrooq Ayed Alenazi, Fatimah Haryoul Al-Anzi, Majidah Qayim Muhayrib Alruwaili, Hanan Mamdouh H. Alrawili, Ahlam Mamdouh H. Alrawili (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Diabetes mellitus is a chronic condition that requires long-term adherence to medication, lifestyle modifications, and regular monitoring to prevent complications. However, non-adherence to treatment remains a significant challenge, leading to poor glycemic control, increased hospitalizations, and higher healthcare costs. Nurses play a vital role in supporting patients with diabetes through education, counseling, continuous follow-up, and individualized care planning. This paper explores the role of nursing in improving treatment adherence among patients with diabetes, highlighting nursing interventions such as patient education, self-management support, motivational interviewing, and monitoring of treatment outcomes. Strengthening nursing involvement in diabetes care can enhance patient engagement, improve adherence, and ultimately lead to better clinical outcomes and quality of life for patients. Introduction Diabetes mellitus is one of the most prevalent chronic diseases worldwide and poses a major public health challenge. Effective management of diabetes depends largely on patients’ adherence to prescribed treatment regimens, including medication use, dietary modifications, physical activity, and blood glucose monitoring. Despite advances in medical treatment, many patients with diabetes struggle to maintain optimal adherence due to factors such as limited health literacy, complex treatment plans, psychosocial barriers, and inadequate support systems. Nurses are at the forefront of diabetes care and have frequent, direct contact with patients across various healthcare settings. Their role extends beyond clinical tasks to include patient education, behavioral support, monitoring of treatment adherence, and coordination of care. Through ongoing patient interaction and holistic assessment, nurses are well positioned to identify barriers to adherence and implement tailored interventions that support self-management. Understanding and strengthening the role of nursing in improving treatment adherence is essential for achieving better glycemic control, reducing complications, and improving overall patient outcomes.